Emotional Reactions to Killing in Remotely Piloted Aircraft Crewmembers During and Following Weapon Strikes. (2nd October 2018) - Chappelle, Wayne; Skinner, Emily; Goodman, Tanya; Swearingen, Julie; Prince, Lillian
Abstract : As part of United States Air Force remotely piloted aircraft (RPA) weapon-strike operations, Predator/Reaper crewmembers participate in the targeting and destruction of enemy combatants and witness the aftermath via live video feed. Although the demand for weapon-strike operations has increased dramatically, the emotional impact of engaging in remote warfare remains unclear. The purpose of this study is to gather both quantitative and qualitative data on the emotional reactions of remote warriors and examine potential occupational (e.g., number of years as an RPA crewmember, prior military experience, prior combat deployments, and total number of weapon-strike missions), demographic (i.e., age, marital status, gender, and dependents living at home), and mission-specific (i.e., target familiarity, mission outcome, and high-definition vs. standard-definition video feed) correlates of negative reactions. Seventy-four RPA crewmembers participated in semi-structured interviews. Relative risk (RR) analyses indicated only witnessing civilian casualties and witnessing nonhuman collateral damage were associated with elevated risk for negative reactions (RR = 1.91, p < .05, 95% confidence interval [CI]: 1.11–3.26, and RR = 1.94, p < .05, 95% CI: 1.14–3.29). Limitations of the study, directions for future research, and potential implications of these findings for selection, training, and post-mission support are discussed.